(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2025)
This study explores the implementation of differentiated instruction (DI) in English language classrooms with mixed-ability learners. By examining theoretical foundations and practical applications, the article highlights how DI strategies enhance student engagement, address diverse learning needs, and improve overall language proficiency. The research includes teacher and learner perspectives, instructional design, and evaluation of outcomes, offering a comprehensive view of DI’s efficacy in diverse educational contexts.